The Archaeological Heritage of Vila Boa de Goiás and projects on the memory and identity of enslaved Black people in Vila Boa de Goiás in the 18th and 19th centuries: The Archaeological Heritage of Vila Boa de Goiás and projects on the memory and identity of enslaved Black people in Vila Boa de Goiás in the 18th and 19th centuries (Revista de História da UEG (REVHIST), 2025)
The main objective of this article is to reflect on the use of material culture in projects related to the memory and identity of enslaved African blacks and Afro-descendants in the 18th and 19th centuries in the urban center of Vila Boa de Goiás, now the city of Goiás. This analysis is based on the ceramic collection obtained from archaeological excavations carried out in the areas where work was carried out to adapt the city of Goiás for the granting of World Heritage Site status by UNESCO. In this period, all the streets of the old urban center of Vila Boa de Goiás and 83 backyards were excavated.Keywords: Urban Heritage. Enslaved Black People. Memory and Identity.